Participatory plant breeding and participatory variety selection - Mamo, Teshale; Asheesh, Singh; Mahama, Anthony A. (Iowa State University Digital Press, 2023)
Formal or conventional plant breeding programs (centralized breeding programs) are often designed to meet specific requirements of different groups of farmers in different growing environments (regions, countries, soil, or climatic conditions). Formal or conventional plant breeding programs have generally been more beneficial to those farmers who either have good crop growing environments or have the capacity to modify growing environments through the application of additional inputs such as fertilizer, pesticides, and irrigation to create more favorable growing conditions for new varieties. However, the results of formal plant breeding may sometimes not meet the requirements of those farmers who grow their crops under marginal soils and high-stress environmental conditions (Sperling et al., 2001) thus necessitating different breeding approaches to be created to meet the needs of poor farmers.